Mindfulness-based programme on the psychological health of pregnant women. Issue 1 (February 2019) - Pan, Wan-Lin; Gau, Meei-Ling; Lee, Tzu-Ying; Jou, Hei-Jen; Liu, Chieh-Yu; Wen, Tzung-Kuen
Abstract: Problem: Preparation of psychological well-being is an important component of antenatal education for childbirth, but few courses focus on this component. Background: The psychosocial health of pregnant women is known to affect perinatal outcomes. Psychosocial stress in women has been associated with increased obstetric interventions and has been shown to affect the health of both mother and child. Aim: To explore the efficacy of an eight-week Mindfulness-Based Childbirth and Parenting programme on reducing prenatal stress, depression, mindfulness, and childbirth self-efficacy. Methods: In this prospective and randomized controlled trial study, 104 women between 13 and 28 weeks gestation were enrolled and assigned randomly into two groups. Participants in the experimental group received mindfulness-based programme and practice-at-home with audio recordings. The comparison group received traditional education classes. Psychological health was assessed at baseline, post-intervention, and 36-week gestation. Findings: Significant differences were seen in both groups in terms of changes over time in stress, depression, childbirth self-efficacy, and mindfulness, as compared with baseline. In gestation week 36, stress scores were slightly higher and childbirth self-efficacy and mindfulness scores were lower for both groups, but all scores were relatively better in the experimental than in the comparison group. Conclusions: Perinatal mental health problems affect mothers, their infants, and society. The eight-week mindfulness programme effectively reduced self-perceived stress and depression and increased childbirth self-efficacy and mindfulness. Future research is needed to explore the potential benefits, mechanisms, and effects on maternal and infant birth outcomes of mindfulness.